Spectrophotometric Determination of Trace Amount of Nitrite in Water with p-Nitroaniline and 1-Naphthol - Khadka, Deba Bahadur; Pachhai, Laxmi (Journal of Institute of Science and Technology, 2015)
A simple, selective and sensitive method for the spectrophotometric determination of nitrite in different natural and waste water samples is applied. Nitrite reacts with p-nitroaniline in the presence of hydrochloric acid to form diazonium cation which is subsequently coupled with 1-naphthol to form a stable azo dye. The ?max for the azo dye is found to be 610 nm. At analytical wavelength 610 nm the Lambert-Beer’s law obeys over the concentration range 0.035-0.123 ?g/ml of nitrite. The correlation coefficient, molar absorptivity and Sandell’s sensitivity of the method were found to be 0.99, 5.24×104 lit.mol-1cm-1 and 8.77×10-4?g cm-2 respectively. The percentage recovery was found to range from 93-109% and the interference of foreign ions was also studied. Journal of Institute of Science and Technology, 2014, 19(2): 89-93